IMPLEMENTATION OF GOOD GOVERNANCE IN JOKO WIDODO'S GOVERNMENT IN PROVIDING PEOPLE'S WELFARE - Rizqi, Retanisa; Rahmaningsih, Aziza Aziz (Sriwijaya Crimen and Legal Studies, 2024)
The implementation of good governance in the second period of Joko Widodo and Ma'ruf Amin aims to improve public welfare. This research analyzes several policies issued by Jokowi so that they can prosper the Indonesian people. This type of research is literature research. Literature study techniques carry out data collection. The results of this study show that the successful implementation of good governance in the Joko Widodo and Ma'ruf Amin administrations in improving public welfare and overcoming the COVID-19 pandemic was carried out through several programs. Some of these successes include controlling the COVID-19 pandemic, maintaining stable economic growth in the era of the COVID-19 pandemic, equitable development throughout Indonesia, showing Indonesia's existence in the international world, and starting the construction of a new national capital. These programs are a paradigm of human development, and the Indonesia-centric program not only makes development in Indonesia for the sake of growth in infrastructure but also encourages changes in the economy, encouraging the country to rise and form. Many governments are democratic, clean, and participatory both domestically and abroad. Through these programs, Jokowi places human welfare as the backbone so as to be able to give meaning to economic sectors that can alleviate poverty, expand opportunities for economic activity, reduce neglect of public services, reduce inequalities and disparities, strengthen social restoration and mental revolution, and eliminate repressive tyranny.